Public politics and environmental education: concepts and contexts in Brazilian academic research - Nery-Silva, Ana Clara; Santana, Luiz Carlos [UNESP] (Federal Univ Rio Grande, Inst Education, 2016)
This article results of research of public policies on environmental education in dissertations and theses in the area, focusing on up steps of development and implementation. The analysis is given on research contained in the catalog of the project ENVIRONMENTAL EDUCATION IN BRAZIL: analysis of academic production (theses and dissertations). Research in public policy have grown considerably in recent years, gaining space as an area of knowledge; but in addition to academic contributions, may help to understand issues of their own political development. In smaller proportions, contributions are observed in research on public policies for environmental education. It is necessary to clarify who are the actors involved in the institutionalization of a policy and relations between them in different socio-political contexts. It is necessary too to understand the indispensability of participatory efforts with social sectors interacting constantly, allowing truly democratic construction.
Keywords: Environmental education; Public policies; Stat of art